2021
DOI: 10.1111/1348-0421.12935
|View full text |Cite
|
Sign up to set email alerts
|

Conserved immunogenic peptides of Ebola glycoprotein elicit immune response in human peripheral blood mononuclear cells

Abstract: In the past 45 years, ebolaviruses have periodically caused epidemics on the African continent. In December 2019, approval of a recombinant vector-based EBOV vaccine, named Ervebo, came as encouraging news; still, there is a long way to go in the development of an accessible, global, and panebolavirus vaccine. The current study expanded our previous in silico work which was conducted on ebolavirus glycoprotein and this resulted in the identification of three potentially immunogenic peptides (P1 -FKRTSFFLWVIILF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In the last two decades, multiple studies have been conducted to develop an ebolavirus vaccine and therapeutics [ 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ]. In 2014, a randomized, double-blind, placebo-controlled, phase I clinical trial demonstrated the safety and immunogenicity of an ebolavirus vaccine [ 165 ].…”
Section: Current Status Of Vaccines and Drugsmentioning
confidence: 99%
“…In the last two decades, multiple studies have been conducted to develop an ebolavirus vaccine and therapeutics [ 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ]. In 2014, a randomized, double-blind, placebo-controlled, phase I clinical trial demonstrated the safety and immunogenicity of an ebolavirus vaccine [ 165 ].…”
Section: Current Status Of Vaccines and Drugsmentioning
confidence: 99%